PROBLEMS OF INCREASING THE ACTIVITY OF STUDENTS WITH LOW ASSESSMENT IN DRAWING - Tadjiyeva Feruza Mukhtorovna (Scholar Express Journals, 2025)
This article describes methodological recommendations on the problems of increasing the activity of students with low drawing skills.
Keywords: knowledge; ability; competence; imagination